Operations management research and cellular manufacturing systems : innovative methods and approaches - Modrak, Vladimir, 1957-; Pandian, R. Sudhakara, 1977- (Hershey PA : Business Science Reference, 2012)
'This book presents advancements in the field of operations management, focusing specifically on topics related to layout design for manufacturing environments'--Provided by publisher.
'Premier reference source'--P. [1] of cover.
Includes bibliographical references and index.
Keywords: Production management; Manufacturing cells; Operations research